Comparative analysis of the value-oriented foundations of the development of higher pedagogical education in China and Belarus - Peytze, U; Palchyk, Henadzi V. (University Pedagogical Journal, 2025)
The results of the comparative analysis of the main strategic materials regulating the training of pedagogical staff in higher education institutions in China and Belarus are presented. The paper identifies common approaches to the development of higher teacher education and its peculiarities in both countries under the conditions of information society.
Keywords: education system; higher pedagogical education; teacher training